2011
DOI: 10.1590/s0100-72032011001200006
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da atividade física na qualidade de vida de mulheres de meia idade: estudo de base populacional

Abstract: ResumoOBJETIVO: Avaliar o impacto da prática de atividade física na qualidade de vida de mulheres de meia idade. MÉTODOS: Estudo de base populacional e corte transversal, que incluiu uma amostra estratificada de 370 mulheres de meia idade entre 40 a 65 anos, recrutadas a partir de uma população de 20.801 mulheres atendidas no período de um ano nas redes básicas de saúde, inseridas nos quatro distritos (Norte, Sul, Leste e Oeste) que compõem o sistema de saúde da cidade de Natal, Rio Grande do Norte, de junho a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
19

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 25 publications
(45 reference statements)
0
14
1
19
Order By: Relevance
“…A study showed that climacteric symptoms appear less frequently (p<0.01) in women who practice physical exercise. 17 Another population-based study, conducted in Natal, state of Rio Grande do Norte, with 365 women aged between 35 and 65 years also found a lower percentage of intense climacteric symptoms (8.0%) in physically active women. 18 A case control study showed that 63.6% of sedentary women had moderate to intense climacteric symptoms and better scores of quality of life were found among women who practiced physical exercise on a regular basis.…”
Section: Discussionmentioning
confidence: 96%
“…A study showed that climacteric symptoms appear less frequently (p<0.01) in women who practice physical exercise. 17 Another population-based study, conducted in Natal, state of Rio Grande do Norte, with 365 women aged between 35 and 65 years also found a lower percentage of intense climacteric symptoms (8.0%) in physically active women. 18 A case control study showed that 63.6% of sedentary women had moderate to intense climacteric symptoms and better scores of quality of life were found among women who practiced physical exercise on a regular basis.…”
Section: Discussionmentioning
confidence: 96%
“…Mulheres com alto grau de escolaridade e maior renda vivenciaram menor sintomatologia em comparação com as de baixa renda e menor grau de escolaridade. [17][18][19][20][21][22][23][24][25][26][27] Nos onze estudos que foram parte integrante desta revisão sistemática, observou--se que a atividade física contribuiu para melhorar as condições de saúde das mulheres no climatério. Portanto, as que praticaram atividade física regular ou aumentaram a intensidade do exercício tiveram menos sinais e sintomas em comparação com as que não praticaram atividade física, recomenda--se uma intervenção terapêutica para as mulheres sedentárias.…”
Section: Discussionunclassified
“…Destaca-se também a influência positiva da atividade física na qualidade de vida das mulheres no climatério nos estudos de coorte e prospectivo. [17][18][19][20][21][22][23][24] Com relação à avaliação metodológica dos artigos desta revisão, verificou-se entre os estudos que realizaram intervenção, ocorreu uma variação de escore entre 13 a 21 pontos com uma média de 57,75 pontos. Quanto aos estudos que não tiveram intervenção, observou-se uma variação de escore entre 12 a 15 pontos com média de 90,14 pontos.…”
Section: Figura 1 Fluxograma Da Seleção Dos Estudos De Acordo Com Asunclassified
“…As a result of this fact, arise consequences such as overload, stress, psychic and physical illnesses, especially the musculoskeletal ones (1) . Contrary to modern day tasks and their drastic consequences, regular physical activity has emerged as a beneficial option for acquiring a healthy life by promoting a range of benefits such as a sense of well-being, reduced depression and anxiety, appetite and body weight control, blood pressure control, relief of musculoskeletal symptoms, among many others (2,3) . For this reason, since the beginning of the 1990s, issues related to the practice of physical activity and the measurement of quality of life, health perception and global well-being, have become a common theme among scholars, presenting the diagnosis of the living conditions of the population in general (4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%